The application of electromagnetic waves in monitoring water infiltration on concrete flat roof: The case of Malaysia. (30th September 2016) - Kot, P.; Ali, A.S.; Shaw, A.; Riley, M.; Alias, A.
Highlights: This paper provides a new idea on detecting water infiltration for concrete roof, which add on to the existing methods. It describes the potential use of microwave technology as an effective non-destructive tool to monitor and investigate leakage of concrete flat roof due to failure of membrane layer. Experiments performed utilized a sensor equipped with essential parameters that enable control to sensor angle, temperature and distance between object and sensor structure and designed to enable numerous measurements in real time. The study determined that microwave technology could be used to identify moisture content in concrete flat roof by analysing properties of the concrete roof and water. This proves to be an effective non-destructive method of determining leakage problems in concrete flat roof in real time before the defects become critical. Abstract: Roof leakages of high-rise buildings involving concrete flat roof design in tropical countries continue to be a serious problem. Currently, exiting methods of detecting potential leaks are mostly destructive to the building material. Although the method of detecting a defect using non-destructive measurement exists, current methods such as infrared thermography, metal detector and humidity meter have varying constraints in their application. This paper describes the potential use of microwave technology as an effective non-destructive tool to monitor and investigate leakage of concrete flat roof due to failure of membrane layer. This study was performed experimentally on flat room structures built for laboratory use and according to Malaysian flat roof concrete proportions standards. Experiments performed utilized a sensor equipped with essential parameters that enable control to sensor angle, temperature and distance between object and sensor structure and designed to enable numerous measurements in real time. The study determined that microwave technology can be used to identify moisture content in concrete flat roof by analysing properties of the concrete roof and water. This proves to be an effective non-destructive method of determining leakage problems in concrete flat roof in real time before the defects become critical.